2015
DOI: 10.1016/j.molcel.2014.12.013
|View full text |Cite
|
Sign up to set email alerts
|

Deacetylation of Nuclear LC3 Drives Autophagy Initiation under Starvation

Abstract: Shuttling of macromolecules between different cellular compartments helps regulate the timing and extent of different cellular activities. Here, we report that LC3, a key initiator of autophagy that cycles between the nucleus and cytoplasm, becomes selectively activated in the nucleus during starvation through deacetylation by the nuclear deacetylase Sirt1. Deacetylation of LC3 at K49 and K51 by Sirt1 allows LC3 to interact with the nuclear protein DOR and return to the cytoplasm with DOR, where it is able to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

30
481
1
6

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 575 publications
(518 citation statements)
references
References 42 publications
30
481
1
6
Order By: Relevance
“…Finally, in the expansion stage, the ATG12-ATG5-ATG16 complex is recruited to the autophagosome membrane where it facilitates the lipidation of microtubule-associated protein 1 light chain 3 (MAP1LC3; also known as LC3) with phosphatidylethanolamine; LC3 is the chief mammalian homologue of yeast Atg8, which is required for the expansion of the isolation membrane. Recent research indicates that the deacetylation and cytosolic translocation of a nuclear pool of LC3 is required for its lipidation with phosphatidylethanolamine during starvation-induced autophagy 14 .…”
Section: Overview Of the Autophagic Pathwaymentioning
confidence: 99%
“…Finally, in the expansion stage, the ATG12-ATG5-ATG16 complex is recruited to the autophagosome membrane where it facilitates the lipidation of microtubule-associated protein 1 light chain 3 (MAP1LC3; also known as LC3) with phosphatidylethanolamine; LC3 is the chief mammalian homologue of yeast Atg8, which is required for the expansion of the isolation membrane. Recent research indicates that the deacetylation and cytosolic translocation of a nuclear pool of LC3 is required for its lipidation with phosphatidylethanolamine during starvation-induced autophagy 14 .…”
Section: Overview Of the Autophagic Pathwaymentioning
confidence: 99%
“…SIRT1 can activate autophagy through various pathways, including modulation of forkhead box transcription factors (FOX), ATG5, ATG7, LC3, and BECN1 (Huang et al., 2015; Lee et al., 2008; Sun et al., 2015). We recently reported that a gradual depletion of this deacetylase with extended ischemia is a causal to mitochondrial dysfunction and cell death (Biel et al., 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Physical linkages between autophagy adaptor proteins via polyubiquitin chains are required for autophagy flux. A recent research demonstrates that the deacetylated nuclear LC3 is transported into the cytoplasm to carry out PE conjugation to pre-autophagic membranes by sequential interaction with Atg7 and Atg3 (34). Especially, nuclear lamina protein lamin B1 degradation is achieved by nucleus to cytoplasm transport degradation that delivers lamin B1 to the lysosome via LC3-lamin B1 interaction in the nucleus (31).…”
Section: Discussionmentioning
confidence: 99%